Fluorescence Recognition of Al(III) Ions by a New Chemosensor Based E-4-((1-(10H-Phenothiazin-2-yl)ethylidene)amino)-N-(pyrimindin-2-yl)benzenesulfonamide - Vijayakumar, P.; Arockia Doss, M.; Nargis Negar, S.; Renganathan, R. (Asian Journal of Chemistry, 2021)
A novel Schiff base derivative E-4-((1-(10H-phenothiazin-2-yl) ethylidene)amino)-N-(pyrimindin-2-yl)benzenesulfonamide (BT) was synthesized and characterized by 1H & 13C NMR, FT-IR and mass spectrometry. Compound BT acts as a detector for Al3+ in ethanol/water HEPES buffer solution (5 mM, pH 7.4, v/v 1:4) at room temperature. The fluorescence intensity observed at 516 nm was increased due to Al3+ ion present with a fluorescence response “turn-on” process, when excited at 290 nm. This shows compound BT is coordinated to Al3+ ion through the NH group and C=NH of the Schiff base blocking the photoinduced transfer (PET) and chelation induced enhanced fluorescence (CHEF) process, to increase the fluorescence intensity of BT. The detection limit of BT was in a micro-molar range for Al3+ ion, confirming high selectivity and sensitivity of BT. The BT-Al3+ ion binding mode and the recognition mechanism of chemosensor were explored by EDTA titration, Job’s plot, Mass and FT-IR analysis. The theoretical support was established by DFT calculations.